Cladophialophora saturnica sp nov., a new opportunistic species of Chaetothyriales revealed using molecular data - Badali, H.; Carvalho, V. O.; Vicente, V.; Attili-Angelis, D. [UNESP]; Kwiatkowski, I. B.; Van den Ende, A. H. G. Gerrits; De Hoog, G. S. (Taylor & Francis Ltd, 2009)
While many members of the black yeasts genus Cladophialophora have been reported to cause diseases in humans, understanding of their natural niche is frequently lacking. Some species can be recovered from the natural environment by means of selective isolation techniques. The present study focuses on a Cladophialophora strain that caused an interdigital tinea nigra-like lesion in a HIV-positive Brazilian child. The fungal infection was successfully treated with oxiconazole. Similar strains had been recovered from the environment in Brazil, Uruguay and the Netherlands. The strains were characterized by sequencing the Internal Transcribed Spacer (ITS) regions and the small subunit (SSU) of the nuclear ribosomal RNA gene, as well as the elongation factor 1-alpha (EF1) gene. Since no match with any known species was found, it is described as the new species, Cladophialophora saturnica.
Keywords: black yeasts; Cladophialophora; cutaneous infection; taxonomy